Major satellite repeat RNA stabilize heterochromatin retention of Suv39h enzymes by RNA-nucleosome association and RNA:DNA hybrid formation - Camacho, Oscar Velazquez; Galan, Carmen; Swist-Rosowska, Kalina; Ching, Reagan; Gamalinda, Michael; Karabiber, Fethullah; De La Rosa-Velazquez, Inti; Engist, Bettina; Koschorz, Birgit; Shukeir, Nicholas; Onishi-Seebacher, Megumi; van de Nobelen, Suzanne; et al. (eLIFE SCIENCES PUBL LTD, 2017)
The Suv39h1 and Suv39h2 histone lysine methyltransferases are hallmark enzymes at mammalian heterochromatin. We show here that the mouse Suv39h2 enzyme differs from Suv39h1 by containing an N-terminal basic domain that facilitates retention at mitotic chromatin and provides an additional affinity for major satellite repeat RNA. To analyze an RNA-dependent interaction with chromatin, we purified native nucleosomes from mouse ES cells and detect that Suv39h1 and Suv39h2 exclusively associate with poly-nucleosomes. This association was attenuated upon RNaseH incubation and entirely lost upon RNaseA digestion of native chromatin. Major satellite repeat transcripts remain chromatin-associated and have a secondary structure that favors RNA:DNA hybrid formation. Together, these data reveal an RNA-mediated mechanism for the stable chromatin interaction of the Suv39h KMT and suggest a function for major satellite non coding RNA in the organization of an RNA-nucleosome scaffold as the underlying structure of mouse heterochromatin.
Keywords: R-LOOPS; HISTONE MODIFICATION; METHYLATION STATES; GENOME INTEGRITY; NONCODING RNA; HIGHER-ORDER; BINDING; TRANSCRIPTION; DNA; CHROMATIN; Life Sciences & Biomedicine - Other Topics